The health and survival of fish exposed to wastewater from Motetema wastewater treatment plant, Sekhukhune District - Mokgawa, Makubu Priscilla (My University, 2020)
The pressing state of South Africa’s freshwater resources due to pollution from the release of raw sewage or poorly treated domestic wastewater, has resulted in the urgent need for the implementation of innovative ways to mitigate this problem. A proposed solution by the Council of Science and Industrial Research (CSIR) is to introduce different cultures of algae in wastewater treatment ponds where facilities have aged and become dilapidated. In turn fish are introduced into sewage maturation pond treated with algae to reduce algal biomass. The assumption being that if fish can survive under these conditions, the nutrients assimilated will be converted into fish biomass when ingested, in an attempt to decrease aquas nutrient loads. The aim of the study was to assess the health and survival of Oreochromis mossambicus exposed to wastewater from the Motetema wastewater treatment plant (WWTP) and to establish the extent to which this species consumes micro-algae within the water column. The aim was accomplished by assessing the consumption of algae by O. mossambicus based on algal cell density counts in fish aquaria and to establish the feeding ratio of fish based on stomach content fullness as well as to monitor the survival rate of O. mossambicus exposed to various concentrations of sewage water over a 96-hour period. To establish fish survival under wastewater conditions, a 96-hour experiment was conducted in glass tanks (60 L), whereby the health and mortality of O. mossambicus exposed to different concentrations of domestic wastewater from Motetema WWTP was investigated. One set of aquariums supplied with compressed air via the use of diffusers while the other set of aquariums were void of aeration so as to simulate conditions at the treatment plant. Treatments comprising of four concentrations of 25, 50, 75 and 100% wastewater and a control of 0% were used. Water quality parameters were monitored every four hours and mortalities were recorded. Water samples were collected twice a day and sent to Capricorn Veterinary laboratory for nutrient analysis. Gill samples were also collected and sent to Onderstepoort Veterinary Institute for histological sections analysis. To assess the consumption of algae, 18 tanks (60 L) were set up in the laboratory, whereby three aquariums served as a control void of algae with the remaining tanks dosed with two algal species (Chlorella vulgaris and Chlorella protothecoides) of concentrations of 33%, 66% and 100%, over a period of ten days. Counts of algal density before and during the course of the experiments were done using a handheld flourometer. Upon mortalities and on the fifth day, fish were randomly selected from fish tanks, euthanised and stomach contents analysed. The stomach of fish was rated based on the percentage fullness and categorised as being empty, ¼ full, ½ full, ¾ full, full or gorged. When mortalities occurred, fish were dissected and their stomach contents analysed for fullness. Upon completion of the trial, two fish per treatment were euthanised and their stomach contents evaluated for algal consumption. Fish remaining at the end of the fish trial were counted and weighed to calculate the weight gain and specific growth rate. Survival rates were also determined. Water quality parameters were monitored three times a day over the duration of the trial. Water samples were collected every second day and send to Capricorn Veterinary laboratory for nutrient analysis. All mortalities were recorded over the duration of the trial period. In exposure and survival trials, physico-chemical parameters of water from the experimental tanks were within the acceptable limit for the growth and survival of O. mossambicus, except for dissolved oxygen and ammonia concentrations. Ammonia levels and mortality rates were significantly higher (p< 0.05) in treatments with wastewater, with ammonia levels exceeding those considered toxic for O. mossambicus. High ammonia concentrations resulted in definite histopathological changes in the gills as well as fish mortalities. After exposure to wastewater moderate signs of aneurism of the gill lamella, mild epithelial lifting, focal hyperplasia and clubbing of the terminal end of the secondary lamellae were recorded. Lesions are explained as a defence mechanism where gills increase the distance between the external environment and the blood, thus serving as a barrier to the entrance of the contaminants. Furthermore, results indicated that effluent levels >25% were detrimental to the fish. Fish survival decreased when exposed to effluent water, with higher number of mortalities recorded in tanks with no aeration. A 100% survival was observed in tanks with 25% treated wastewater in both aerated and non-aerated aquariums. The presence of fish mortalities in treatments >25 domestic wastewater shows that conditions at Motetema WWTP will be unfavourable for fish. Thus, results from the study indicate that domestic wastewater would need to be diluted to less concentrated levels to ensure the survival of fish and mechanical aerators needs to be deployed to increase oxygen levels in treatment ponds. Water quality parameters for the second set of experiments fell within the recommended range for the growth and survival of fish. However, low oxygen levels were recorded from the control group with minimum values of 1.8 mg/l and maximum concentrations of 3.6 mg/l. Furthermore, temperature and pH ranges recorded during this study fell within the desired range for growth and reproduction of Chlorella vulgaris and Chlorella protothecoides. Nutrient concentration (phosphates, sulphates and nitrate) for this study were low, however ammonia and nitrite were above the acceptable level for fish growth and survival. The presence of fish resulted in increased levels of ammonia. High ammonia levels were not mitigated by algae in the tanks. However, the high ammonia levels decreased with the increasing number of fish mortalities. There were slight decreases in chlorophyll-a concentrations over the study period, from tanks comprising of algae and, tanks comprising of algae and fish. Decreases in chlorophyll-a concentrations in tanks with fish were linked to consumption of algae by the fish. This was verified by the presence of algae in the stomach of fish euthanised during and at the end of the experiment. In tanks without fish, decreases in chlorophyll-a concentrations could be attributed to plankton die offs, as aquariums had algae that had settled at the bottom of the tanks. Although, consumption of algae by fish was observed in this study, no full stomachs were recorded over the experiment period. Tanks with 66% algal concentrations had low survival rates. Better survival was observed from treatments with 33% algal concentrations. Toxic secretions could have attributed to the high mortality rate or low survival rates during the study period in tanks with 66% and 100% algal concentrations. In addition to this, ammonia and nitrite values that were above tolerable limits for fish could have also contributed to the high mortality rates (>80%). The use of fish in the tanks as a means to assimilate the algae, seemed to have an opposite effect than the desired one. As the presence of fish in tanks increased ammonia levels, therefore, the effluent would need to be further treated before it can be re-used or released into the environment. Further experiments would need to be conducted to establish whether negative influences could be neutralised, when other species such as Scenedesmus spp. are used together with Chlorella spp. for the treatment of wastewater, in order to make the environment suitable for fish survival.
Thesis (M.Sc. (Zoology)) -- University of Limpopo, 2020
Keywords: Land treatment of wastewater; Fish culture; Fish culture - Water reuse